Slope stability case studies and analyses - Tan, Wie Guan. (2011)
Major development is seen in geotechnical aspect of slope stability analyses over the past few decades. Traditionally, conventional limit equilibrium methods such as Bishop Simplified, Spencer, Morgenstern and Price, Janbu are widely used in practice. Due to the widespread of more sophisticated electrical equipments and components, better soil analyzing programs have been produced. One such method that utilizes this is finite element method. More recognition has been given to this method of analyzing slope since it provides comprehensive details of the stress-strain behaviour of soil. Finite element method using shear strength reduction technique is used to determine the factor of safety.